Use of online sources of information for dental prac-tice among private dental practitioners in Bangalore â€“ a cross sectional survey - Reddy, Mayur Nath; K, Hemalatha (International Journal of Dental Research, 2017)
Introduction: The Internet seems to provide a new opportunity to overcome problems of access and provide clinically appropriate information to practitioners. However, while use of the Internet for clinical information has grown substantially in recent years. Access to the Internet has been improving rapidly for all professional groups. Dental professionals in clinical practice have been increasing opportunities to obtain information for clinical decision-making from a variety of resources, including a growing availability through online technology.Objectives:1)Â Â Â Â Â  To assess the frequency of utilizing online sources of information for practical guidance.2)Â Â Â Â Â  To assess the influence of online sources of information on practical guidance.Materials and Methods: A Cross-sectional survey was carried out among 386 private dental practitioners in Bangalore city. A self-administered, structured questionnaire containing 16 items was used (including demographic details). Cronbach's Î± was found to be 0.87 for each item. Statistical analysis was done using chi-square test.Results: 81.6% (n=315) of private dental practitioners use the Internet as their source of information for clinical practice. Only 18.4% (n=71) do not use, the main reason for not using internet is lack of time and it is too complicated to use. 44.8% (n=173) rated on online source as most influential and 45.6% (n=176) frequently using online source for guidance. Information was primarily sought on patient education, oral disease, updates on common disease, and diagnosis. Medline was the most frequently accessed source.Conclusion: A relatively large proportion of dental practitioners uses information from online sources for practical guidance. The Internet could be a valuable medium for the information, provided, that its use is accompanied by training in the identiï¬cation, use, and application.Â